2017
DOI: 10.21776/ub.jitode.2017.005.03.07
|View full text |Cite
|
Sign up to set email alerts
|

Private Business’ Roles as Stakeholders in Developing Surabaya as Tourism Destination

Abstract: According to UNWTO report, the international tourist arrivals reached 1.2 billion people in 2016. There was 5% growth in the developed countries and 2% growth in the developing countries, including Indonesia. In 2016, Indonesia welcomed 11.52 million international tourists. As the second biggest city in Indonesia, Surabaya has important roles for the country. Receiving around 564,000 international tourists in 2016, Surabaya had changed into a tourism destination. The development began in 2005 when Surabaya Tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The study of network governance in the Indonesian tourism policy has been previously conducted. Indrianto et al [8] conducted a study about the roles of the government as a stakeholder in developing destinations in Surabaya, East Java Furthermore, a study carried out by Nusantara et al [10] also showed that two different tourism development approaches in Surakarta resulted in relatively balanced stakeholder assessments. This is because stakeholders in Surakarta maintain a differentiated and balanced view of the respective impacts of the different tourism policies and their development approaches.…”
Section: Iapamentioning
confidence: 99%
“…The study of network governance in the Indonesian tourism policy has been previously conducted. Indrianto et al [8] conducted a study about the roles of the government as a stakeholder in developing destinations in Surabaya, East Java Furthermore, a study carried out by Nusantara et al [10] also showed that two different tourism development approaches in Surakarta resulted in relatively balanced stakeholder assessments. This is because stakeholders in Surakarta maintain a differentiated and balanced view of the respective impacts of the different tourism policies and their development approaches.…”
Section: Iapamentioning
confidence: 99%